Genome-Wide Identification, Localization, and Expression Analysis of Proanthocyanidin-Associated Genes in Brassica - Liu, Xianjun; Lu, Ying; Yan, Mingli; Sun, Donghong; Hu, Xuefang; Liu, Shuyan; Chen, Sheyuan; Guan, Chunyun; Liu, Zhongsong (Frontiers in Plant Science, 2016)
Proanthocyanidins (PA) is a type of prominent flavonoid compound deposited in seed coats which controls the pigmentation in all Brassica species. Annotation of B. juncea genome survey sequences showed 72 PA genes; however, a functional description of these genes, especially how their interactions regulate seed pigmentation, remains elusive. In the present study, we designed 19 primer pairs to screen a bacterial artificial chromosome (BAC) library of B. juncea. A total of 284 BAC clones were identified and sequenced. Alignment of the sequences confirmed that 55 genes were cloned, with every Arabidopsis PA gene having 2-7 homologs in B. juncea. BLAST analysis using the recently released B. rapa or B. napus genome database identified 31 and 58 homologous genes, respectively. Mapping and phylogenetic analysis indicated that 30 B. juncea PA genes are located in the A-genome chromosomes except chromosome A04, whereas the other 25 genes are mapped to the B-genome chromosomes except B05 and B07. RNA-seq data and Fragments Per Kilobase of a transcript per Million mapped reads (FPKM) analysis showed that most of the PA genes were expressed in the seed coat of B. juncea and B. napus, and that BjuTT3, BjuTT18, BjuANR, BjuTT4-2, BjuTT4-3, BjuTT19-1, and BjuTT19-3 are transcriptionally regulated, and not expressed or downregulated in yellow-seeded testa. Importantly, our study facilitates better understanding of the molecular mechanism underlying Brassica PA profiles and accumulation, as well as in further characterization of PA genes.